The Seasonal Distribution of Molluscan (Bivalvia and Gastropoda) Biodiversity in Riva Stream (Istanbul) - Nilay Dökümcü; Serap Koşal Şahin (Aquatic Sciences and Engineering)
Mollusk samples were collected between March 2018 and January 2019 through seasonal sampling at five stations [Riva (ST1), Kuzdere (ST2), Kanlıdere (ST3), Atdosun (ST4), Değirmendere (ST5)] of Riva Stream (Istanbul). In the study, 7,073 individuals, 7 taxa [1 species belonging to Prosobranchia (Bithynia sp.), 3 species belonging to Pulmonata (Planorbis planorbis (Linnaeus, 1758), Physella acuta (Draparnaud, 1805) and Gyraulus albus (O. F. Müller, 1774) and 3 species belonging to Bivalvia [Pisidium casertanum (Poli 1791), Pisidium amnicum (Muller, 1774) and Sphaerium corneum (Linnaeus, 1758)] were determined. Considering the dominance (%) of taxa, Bithynia sp. was determined as the most dominant species among all stations (5,479 individuals (77.46%)). During sampling, various environmental variables [depth (cm), width (cm), flow rate (m/s), water temperature ( oC), dissolved oxygen (%), pH, conductivity (μS/cm), salinity (ppm), NH4 -N (mg/L), NO3 -N (mg/L), NO2 -N (mg/L), PO4 -P (mg/L), TP (mg/L) and TSS (g/L)] were measured. The relationship between environmental variables and taxa was determined using Canonical Correspondence Analysis (CCA) using the Past Statistics Program, version 4.02. The clustering relationship between the five sampling stations and the unweighted pair group method (UPGMA) with arithmetic mean was show